2020
DOI: 10.30998/scope.v5i1.6568
|View full text |Cite
|
Sign up to set email alerts
|

The Implementation of Duolingo Mobile Application in English Vocabulary Learning

Abstract: The purposes of this research are as follows: to obtain data and to analyze the effects of the implementation of Duolingo mobile application in English vocabulary. The research was held at SDN 02 Ciputat. All data variables were taken through tests. For vocabulary mastery tests, the data was taken in the questionnaires form. The method used was to conduct a system quality test (Software Quality Assurance) of software quality based on the factors and the criteria established. The data shows that the application… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…Foreign scientists have addressed the issue of implementing mobile applications for improving English language communicative competence of university students. I. Ari et al [13] describe the process of implementing Duolingo mobile application with the aim of improving students' English vocabulary. D. Assanova and A. Prlepessova [14] prove the importance of educational mobile apps in learning English for non-linguistic specialties.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Foreign scientists have addressed the issue of implementing mobile applications for improving English language communicative competence of university students. I. Ari et al [13] describe the process of implementing Duolingo mobile application with the aim of improving students' English vocabulary. D. Assanova and A. Prlepessova [14] prove the importance of educational mobile apps in learning English for non-linguistic specialties.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Mastery of vocabulary is important in learning English. According to (Zahedi & Abdi, 2012) as cited in (Irawan et al, 2020), their writing research states that one of the components to mastering English as a foreign language is vocabulary mastery. From this statement, it can be concluded that vocabulary mastery is the key in learning a language, and it means that without studying the vocabulary, the students would be impossible to communicate effectively.…”
Section: Vocabulary As the Main Component Of Englishmentioning
confidence: 99%
“…Media is a tool used by teachers in the teaching and learning process to facilitate and provide teaching materials to students. According to (Arsyad, 2011) Learning media is everything that is used as a learning resource and can be used to convey messages from sender to receiver so that they can feel interest, curiosity in such a way that the learning process takes place and further explained that learning media is a tool in the learning process both inside and outside class (Irawan, 2020).…”
Section: Teaching Media For Effective Vocabulary Learningmentioning
confidence: 99%
See 2 more Smart Citations